(untitled) - Poliakova, Adela (Doprava a spoje, 2010)
The paper brings simply information about a process of registration and application of forwarding company. The AEO certificate is a sign for customers that the forwarding company takes care about safety and responsibility of its service. The AEO certificate is possible to take like a quality mark and the advantage in competitor's fight.